Information management in the police force of the Slovak Republic - Dworzecki, Jacek; Hryszkiewicz, Dominik (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article presents the process of information management within the realms of the functioning of the Police Corps in the Slovak Republic. The described solutions concern broadly understood social communication, which is the participation of press departments of this largest military force responsible for safety and public order in our southern neighbour. Within the article both organizational and doctrinal solutions were presented in the scope of contacts with media, information flow between individual departments, and organizational units of the Police Corps.
Keywords: Słowacja; Korpus Policji; zarządzanie informacją